Arrays and Array Methods in Global Seismology 2009
DOI: 10.1007/978-90-481-3680-3_8
|View full text |Cite
|
Sign up to set email alerts
|

The European Upper Mantle as Seen by Surface Waves

Abstract: We derive a global, three-dimensional tomographic model of horizontally and vertically polarized shear velocities in the upper mantle. The model is based on a recently updated global database of Love-and Rayleigh-wave fundamental-mode phase-anomaly observations, with a good global coverage and a particularly dense coverage over Europe and the Mediterranean basin (broadband stations from the Swiss and German seismic networks). The model parameterization is accordingly finer within this region than over the rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(49 citation statements)
references
References 52 publications
(75 reference statements)
8
41
0
Order By: Relevance
“…These findings generally corroborate the results obtained in previous tomographic studies [ Wortel and Spakman , 1992; Lorenz et al , 1997; Martin et al , 2005, 2006]. Our results are in qualitative agreement with S velocity model derived from inversion of surface waves by Boschi et al [2009] who found a slow heterogeneity under the Carpathians, underlain by a fast one, with the transition at ∼100–150 km depth. The tomography investigations using teleseismic data [ Wortel and Spakman , 2000; Martin et al , 2006] pointed out a well‐defined high‐velocity body extending down to a depth of about 400 km.…”
Section: Discussion Of the Resulting Velocity Patterns And Interpretasupporting
confidence: 93%
“…These findings generally corroborate the results obtained in previous tomographic studies [ Wortel and Spakman , 1992; Lorenz et al , 1997; Martin et al , 2005, 2006]. Our results are in qualitative agreement with S velocity model derived from inversion of surface waves by Boschi et al [2009] who found a slow heterogeneity under the Carpathians, underlain by a fast one, with the transition at ∼100–150 km depth. The tomography investigations using teleseismic data [ Wortel and Spakman , 2000; Martin et al , 2006] pointed out a well‐defined high‐velocity body extending down to a depth of about 400 km.…”
Section: Discussion Of the Resulting Velocity Patterns And Interpretasupporting
confidence: 93%
“…In Fig. S7 of the supplementary material we compare the isotropic shear wavespeed of EU 50 at a depth of 100 km with five surface-wave models, namely, EPmantle (Schivardi and Morelli, 2011), Chang2010 (Chang et al, 2010), S2.9EA (Kustowski et al, 2008b), LRSP30EU02 (Boschi et al, 2009) and CUSDT (Shapiro and Ritzwoller, 2002). Model EU 50 correlates well with these five models at this shallow depth.…”
Section: Comparisons With Previous Modelsmentioning
confidence: 90%
“…Receiver functions, in contrast, are used for the detection of sharp crustal and upper mantle discontinuities beneath seismic stations. (Trampert and Woodhouse 1995;Masters et al 2000;Zhou et al 2006;Peter et al 2008;Lebedev and van der Hilst, 2008;Boschi et al, 2009;Ritsema et al, 2011;Khan et al, 2011) and regional scales (Ritzwoller and Levshin 1998;Villasenor et al, 2001;Bruneton et al, 2004;Levshin et al, 2007;Weidle and Maupin, 2008;Legendre et al, 2012;Rickers et al, 2013), and also in body wave tomography on global (e.g. Grand et al, 1997;Grand, 2002) and regional (Spakman, 1990) scales.…”
Section: Brief Overview Of Seismic Studies Of the European Lithospherementioning
confidence: 99%